(untitled) (International relations and international law Journal, 2016)
In article it is considered the main problems of political crisis after falling of Mubarak in Egypt. Fight for the future of Egypt didn’t stop for a minute. Morsi’s actions – drawing blow to judicial system – demonstrated that he intends to make after the adoption of the new constitution. Between liberal and Islamic forces of Egypt grew tension in connection with disagreements concerning the future of the country. In article it is also described as at the beginning of July, 2013 in Egypt there was a military coup as a result of which the president Mohamed Morsi was detached. In Egypt it was declared stay of action of the constitution. Within «road map» on a country conclusion from crisis the special commission which began development of the text of the new constitution was created. It was declared carrying out early presidential elections in Egypt. In May, 2014 Abdel Fatah as-Sisi won an election of the president of Egypt. Problems of Egypt are obvious and expectations of changes are huge, but that we observe today gives to hope for positive changes within the next years.